2015
DOI: 10.18433/j3wk65
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Analysis of Methadone in Exhaled Breath Condensate Using a Validated LC-UV Method

Abstract: -Purpose. A combined microextraction and separation method is presented for the determination of methadone in exhaled breath condensate (EBC) which is a promising non-invasive biological component for monitoring drug concentrations. Methods. In this work, dispersive liquidliquid microextraction (DLLME) and ultrasonic liquid-liquid microextraction (ULLME) procedure coupled with a validated liquid chromatography method were used for analysis of methadone in EBC collected using an in-house cold trap setup. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 35 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…DLLME and USAEME not only reduce consumption of organic solvent, but also reduce equilibration time because of the increased contact area between two immiscible phases. Recently, some DLLME-based methods combined with spectrofluorimetry, 26 high performance liquid chromatographic-ultraviolet (HPLC-UV), 27 capillary electrophoretic-ultraviolet (CE-UV) 28,29 have been reported for determination of drugs in human plasma and urine samples. In a previous work, the applicability of the DLLME method as an efficient microextraction technique for bioanalysis was proposed and its results were compared with those of USAEME.…”
Section: Introductionmentioning
confidence: 99%
“…DLLME and USAEME not only reduce consumption of organic solvent, but also reduce equilibration time because of the increased contact area between two immiscible phases. Recently, some DLLME-based methods combined with spectrofluorimetry, 26 high performance liquid chromatographic-ultraviolet (HPLC-UV), 27 capillary electrophoretic-ultraviolet (CE-UV) 28,29 have been reported for determination of drugs in human plasma and urine samples. In a previous work, the applicability of the DLLME method as an efficient microextraction technique for bioanalysis was proposed and its results were compared with those of USAEME.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted by Khoubnasabjafari et al monitoring drug concentrations dengan extraction and analysis of methadone in exhaled breath condensate using a validated liquid chromatography ultraviolet method [27]. From the study, it was found that the percentage of other substance use in patients of the largest MMT program was benzodiazepine group medicine as many as 25 patients (64.1%), can be seen in Table 2.…”
Section: The Effect Of Other Substances On Retentionmentioning
confidence: 99%
“…For example, Göen et al used a clean-up and preconcentration step for 3-nitrotyrosine measurement in EBC using a C 18 cartridge, before LC-MS/MS analysis [4]. In addition, Khoubnasabjafari et al used two sample preconcentration/preparation procedures (i.e., dispersive liquid-liquid microextraction and ultrasonic liquid-liquid microextraction) before HPLC-UV analysis for determination of methadone in the EBC samples [5]. Karyakina et al reported a flow-injection analysis electrochemical system coupled with an ion-exchange preconcentration column (filled with Strata SAX sorbent-silica gel with quaternary ammonium substituents, Phenomenex, CA, USA) for the lactate sensing in EBC of patients with lung diseases [6].…”
Section: Characteristics Of Exhaled Breath Condensatementioning
confidence: 99%